Preparation of magnetic MIL-101 (Cr) for efficient removal of ciprofloxacin - KERKEZ KUYUMCU, ÖZGE (SPRINGER HEIDELBERG, 2017)
Metal organic frameworks are widely used as adsorbent materials in recent years. In this study, the most prepared metal organic framework MIL-101 was prepared by hydrothermal method and featured magnetic property using co-precipitation method Fe3O4. Then, the prepared composite (MIL-101/Fe3O4) was first characterized using XRD, FTIR, SEM-EDS, and surface area analysis, then was used for the adsorptive removal of the most used antibiotic, ciprofloxacin (CIP). The effect of different adsorption variables which may affect the removal of CIP by MIL-101/Fe3O4 was investigated, as well as their adsorbent quantity, initial CIP concentration, pH, temperature, and contact time. The non-linear Langmuir and Freundlich isotherm were applied to experimental data. It was observed that rising solution temperature decreases adsorption efficiency, as the maximum adsorption uptake value was 63.28 mg g(-1) at 298 K and 22.93 mg g(-1) at 313 K, indicating the exothermic nature of the adsorption. The adsorption was studied kinetically and found to follow the pseudo-second-order kinetic model. The desorption of CIP from the MIL-101/Fe3O4 was investigated using three different eluents, and the results showed that phosphate-buffered solution was the most effective desorption eluent.
Keywords: MIL-101; Magnetic materials; Ciprofloxacin; Adsorption; METAL-ORGANIC FRAMEWORK; WALLED CARBON NANOTUBES; AQUEOUS-SOLUTION; ADSORPTION BEHAVIOR; MESOPOROUS CARBON; FACILE SYNTHESIS; WATER; MECHANISMS; ALUMINUM; SORPTION